Grammatical Accuracy in Translating Direct Speech: A Comparison between Professionals and EFL Students - Alfarina, Larida; Hartono, Rudi (Allure Journal, 2025)
This study investigates the grammatical accuracy in translating direct speech from This study investigates the grammatical accuracy in translating direct speech from English to Indonesian by comparing the performance of professional translators with that of EFL (English as a Foreign Language) students. The research utilizes 20 carefully selected excerpts from "The Valley of Fear" by Arthur Conan Doyle. Fifteen final-year English education students’ translations were meticulously assessed against an officially published version, allowing for a robust comparative analysis. A qualitative comparative approach was employed, utilizing a rubric grounded in Nababan’s (2012) translation quality model, which evaluates critical aspects such as tense usage, agreement, sentence structure, and punctuation. The findings reveal significant insights into the translation capabilities of EFL students. While students exhibited moderate accuracy in tense and agreement, they encountered considerable challenges with punctuation and sentence structure. For instance, the nuanced use of commas and quotation marks in direct speech, which can dramatically alter the meaning and flow of dialogue, often eluded the students. In contrast, professional translators demonstrated a higher level of grammatical cohesion and a lower frequency of errors. This disparity underscores the complexities involved in translating literary texts, where the subtleties of language play a pivotal role in conveying the author's intent and character voice. Moreover, the study emphasizes the pressing need for grammar-focused and genre-specific training within translation education.